A case of Fournier’s gangrene caused by Rothia dentocariosa - Taylan Önder; Sevil Alkan; Seyhan Tezcan (Iberoamerican Journal of Medicine, 2023)
We report a case of Fournier's gangrene rescued by debridement. A 40-year-old male patient had a 2x2 cm draining ulcer and 1x2 cm necrotic area in the scrotum for about a month. The patient was diagnosed with Fournier's gangrene. Septic shock and disseminated intravascular coagulation were absent. Computed tomography scan showed soft tissue gas in the scrotum but no gas in the retroperitoneal space or abdominal wall. Debridement was performed. Gangrene of the scrotum and necrosis of the testicle was also seen. Rothia dentocariosa was isolated in extracted wound cultures. He was saved after debridement and administration of strong antibiotics. This is the first case of Fournier's gangrene caused by R. dentocariosa in the available literature.